1997
DOI: 10.1016/s0165-5876(97)00144-4
|View full text |Cite
|
Sign up to set email alerts
|

Management of infantile subglottic hemangioma: laser vaporization, submucous resection, intubation, or intralesional steroids?

Abstract: The infantile subglottic hemangioma can be treated in various ways. The results of the treatment used in the Sophia Children's Hospital, intralesional steroids and intubation (IS + I), are discussed and compared with the results of other current treatment methods: CO2 laser vaporization, submucous resection and intubation alone. A total of 18 infants were treated for subglottic hemangioma in our hospital: ten with IS + I alone, five were first treated with systemic therapy and later with IS + I alone and three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 25 publications
0
38
0
2
Order By: Relevance
“…317,[326][327][328][329][330] However, many clinicians have now reported success and low complication rates using propranolol in the management of airway IHs. 326,[331][332][333][334][335][336] Although the optimal dose and appropriate duration of therapy remain uncertain, most clinicians are dosing the drug as they would for cutaneous IH.…”
Section: Highlights Of This Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…317,[326][327][328][329][330] However, many clinicians have now reported success and low complication rates using propranolol in the management of airway IHs. 326,[331][332][333][334][335][336] Although the optimal dose and appropriate duration of therapy remain uncertain, most clinicians are dosing the drug as they would for cutaneous IH.…”
Section: Highlights Of This Sectionmentioning
confidence: 99%
“…Successful management has been achieved in 77% to 87% of cases with the use of intralesional steroids. 317,327 Airway IHs causing focal obstruction may be addressed surgically by a subtotal endoscopic approach by using a microscope or telescope or by total excision through an open approach. Subtotal approaches generally use a laser 317 or rotarypowered instrument.…”
Section: Highlights Of This Sectionmentioning
confidence: 99%
“…Hoeve et al 16 reported an average intubation of 37 days in 14 successful cases (out of a total of 18 cases) and an average intubation of 54 days in the failed cases. One patient was intubated for 129 days.…”
Section: Local Steroid Injection and Intubationmentioning
confidence: 99%
“…Sin embargo, aquellos pacientes que respondían debían permanecer con altas dosis de corticoides (3 mg/kg/día) por tiempos prolongados con los efectos colaterales propios de la corticoterapia prolongada. Existen reportes de infiltraciones intralesionales de corticoides con una tasa de éxito de 83%, pero esta técnica no ha sido adoptada globalmente, ya que los pacientes deben permanecer intubados por un tiempo promedio de cincuenta días y porque se requieren múltiples aplicaciones, lo cual eleva el costo del tratamiento 9 .…”
Section: Figuraunclassified